Social theory as politics in knowledge - Lehmann, Jennifer M., 1956- (Amsterdam ; Boston : JAI, 2005)
This volume discusses, and manifests, three interrelated perspectives in social theory. First, that all knowledge, including scientific knowledge, is theoretical: there are alternative perspectives, or theories, about any phenomenon. Second, that all knowledge, including scientific knowledge is political: these alternative perspectives are contested, as they are related to different groups with different interests. Third, that all knowledge, including scientific knowledge, is social: alternative perspectives have alternative social causes and alternative social effects.
Includes bibliographical references.
Description based on print version record.
Keywords: Political sociology; Sociology -- Philosophy; Social theory; Social Science -- Sociology -- General